Pengaruh Habit of Mind dan Self-Efficacy terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Agustina, Novia; Munandar, Dadang Rahman (Lattice Journal : Journal of Mathematics Education and Applied, 2022)
This study aimed to determine the effect of the habit of mind and self-efficacy on students' mathematical problem-solving abilities. The approach used is quantitative with the ex post facto method. The population in this study were all eighth-grade students at one of the SMP in Bekasi city. The sample taken amounted to 69 students. The instrument used is a test in the form of a description of the problem-solving ability, a habit of mind questionnaire, and a self-efficacy questionnaire. Simple and multiple linear regression analysis was used to analyze the data in this study. Based on the results of the study, it can be concluded that the influence of habit of mind on mathematical problem-solving abilities is equal to 22.1%, and there is an influence of self-efficacy on mathematical problem-solving abilities that is equal to 22.9%. Furthermore, there is an influence of habit of mind and self-efficacy on mathematical problem-solving ability, which is 34.7%. Thus, it is found that habits of mind and self-efficacy significantly affect students' mathematical problem-solving abilities.Tujuan penelitian ini adalah mengetahui pengaruh habit of mind dan self-efficacy terhadap kemampuan pemecahan masalah matematis siswa. Pendekatan yang digunakan adalah kuantitatif dengan metode ex post facto. Populasi dalam penelitian ini yaitu seluruh siswa kelas VIII di salah satu SMP di Kota Bekasi. Sampel yang diambil berjumlah 69 siswa. Instrumen yang digunakan adalah tes berbentuk soal uraian tentang kemampuan pemecahan masalah, angket habit of mind, dan angket self-efficacy. Analisis regresi linear sederhana dan berganda digunakan untuk menganalisis data pada penelitian ini. Berdasarkan hasil penelitian dapat diambil kesimpulan bahwa terdapat pengaruh habit of mind terhadap kemampuan pemecahan masalah matematis yaitu sebesar 22,1%, terdapat pengaruh self-efficacy terhadap kemampuan pemecahan masalah matematis yaitu sebesar 22,9%. Selanjutnya, terdapat pengaruh habit of mind dan self-efficacy terhadap kemampuan pemecahan masalah matematis yaitu sebesar 34,7%. Dengan demikian, diperoleh bahwa habit of mind dan self-efficacy berpengaruh signifikan terhadap kemampuan pemecahan masalah matematis siswa.